Multiple Distant Cutaneous Metastasis: An Uncommon Presentation of a Common Malignancy - Kishore, Manjari; Gupta, Prajwala; Malhotra, Purnima; Aggarwal, Lalit; Bhardwaj, Minakshi (Annals of Pathology and Laboratory Medicine, 2018)
Cutaneous metastasis from carcinoma breast in areas outside the chest wall is very rare. We present a case of young female with bilateral breast swellings with a clinicoradiological diagnosis of Fibroadenoma wherein FNAC proved useful in establishing the diagnosis of bilateral breast carcinoma with distant cutaneous metastasis.